SENYAPAN DAN KILIR LIDAH BERDAMPINGAN DALAM PRODUKSI UJARAN - Pangesti, Fida (University of Brawijaya, 2019)
This study examines sequencial hesitation disfluencies and slip of the tongue in Bahasa Indonesia from psycholinguistic reviews. The aim is to find (1) the type of sequencial hesitation disfluencies and slip of the tongue and (2) the relation between hesitation disfluencies and slip of the tongue in a speech production. The data in this study were taken from spontaneous speeches in the speech titles Mata Najwa and Kick Andy with the reading method and then analyzed with a slime technique. This study produced two findings. First, the type of sequencial hesitation disfluencies and slip of the tongue, namely (a) Freudians Slip- Filled Pauses, (b) Freudian Slip-Silence Combinations, (c) Blend-Filled Pauses, (d) Anticipation — Filled Pauses, (e) Transposition Filled Pauses, and (f) Transposition-Silence Combinations. Second, Hesitation Disfluencies arises as a result of slip of the tongue because speakers need additional time to retrieve the required vocabulary.